Creative Islamic Education Learning Media: A Collaboration of the Open-Ended Approach and the Think Pair Share Model - M Rindu Fajar Islamy (CV. Creative Tugu Pena, 2025)
This study aims to examine and develop Islamic Education (PAI) learning media based on the Open-Ended Approach integrated with the Think Pair Share (TPS) model to enhance students’ creative thinking skills. Creative thinking is one of the essential 21st-century skills, yet it remains relatively low in Indonesia. According to The Global Creativity Index 2015, Indonesia ranks 115th out of 139 countries. This low performance is influenced by non-innovative teaching methods, unsupportive learning environments, limited teacher competence, and suboptimal use of technology. Vildan Celik, a global education practitioner, emphasizes that teachers’ lack of ability to design innovative learning experiences significantly hampers the development of student creativity. The integration of the Open-Ended Approach with TPS is expected to foster students’ creativity by providing flexible thinking opportunities, encouraging active discussion, and promoting idea sharing in problem-solving. This qualitative research employed a development design involving expert validation and student response analysis. Data were collected through in-depth interviews with PAI lecturers and students concerning the developed learning materials and instructional videos. The findings reveal that integrating the Open-Ended Approach with TPS in Islamic Education learning media effectively stimulates creative thinking through: (1) contextual learning materials that encourage multiple solutions, (2) interactive video elements that foster critical thinking, and (3) collaborative learning structures that facilitate knowledge construction. Expert validation confirmed that the materials met fundamental criteria with suggestions for contextual improvement. Student responses indicated positive engagement with multimedia elements and collaborative learning approaches.